Shilajitin Cancer Treatment: Probable Mode of Action - Verma, Akhilesh (International Journal of Pharmaceutical & Biological Archive, 2016)
Cancer is a horrible disease which is leadingcause of death after cardiovascular disease. The principal etiological factor for cancer comprise mutagens, toxins, free radicals, radiations apart from many other causes, inflammation can increase the threat of cancer development and progression. Indian medical system i.e.Ayurveda was used as a means for the prevention of the effects of aging and generation of disease. Shilajitis a potent rejuvenator and havingadaptogenic action. Since thousands of years many therapeutic assets have been ascribed to it, some pharmacological properties have been verified by modern scientific evaluation. Shilajit has been attributed with many miraculous restorative properties,improve the quality of life and it seemed to cure all diseases. Shilajit is a brownish-blackcoloredherbo-mineral medicine, collected from the high altitude mountains of many parts of the world. In this review we have focused on the cancer preventive and therapeutic properties of active principles ofShilajit. Shilajit possess anti-inflammatory, antioxidant, anti-mutagenic, immuno-modulator, antitumor, and photo-protective properties. These assets make Shilajit useful agents for cancer therapy and prevention.